2020
DOI: 10.1017/s175173111900243x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a riboflavin source suitable for use in organic broiler diets on performance traits and health indicators

Abstract: Riboflavin (vitamin B2) is essential for monogastric animals. It is mainly produced by recombinant microorganisms (Candida famata, Bacillus subtilis and Ashbya gossypii). The availability of genetically modified organism (GMO)-free riboflavin, obligatory in European organic agriculture, is a major issue. Besides, requirements for organic livestock might differ from conventional production because other genotypes and feed formulations are used. The effects of a fermentation suspension with a high native content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…However, the true reason for the decrease in the present study remained unclear. In other experiments with similar diet formulations, conducted by some of the authors of this article, the riboflavin content of the feed was not found to decrease during a 10-months storage period (Lambertz et al 2020). It is important to note that, in the present study, from week 8 onwards, the difference in the riboflavin concentrations between R3.0 and R4.5 became rather small.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, the true reason for the decrease in the present study remained unclear. In other experiments with similar diet formulations, conducted by some of the authors of this article, the riboflavin content of the feed was not found to decrease during a 10-months storage period (Lambertz et al 2020). It is important to note that, in the present study, from week 8 onwards, the difference in the riboflavin concentrations between R3.0 and R4.5 became rather small.…”
Section: Discussionsupporting
confidence: 46%
“…Riboflavin is generally not synthetically produced, but is derived from microorganisms like bacteria or yeasts, and in the current industrial processes, these microorganisms are usually genetically modified. However, organic production relies on inputs from non-GMO sources (Council of the European Union 2018; Lambertz et al 2020Lambertz et al , 2021. This is relevant as riboflavin is almost exclusively produced on the basis of genetically modified microorganisms, which implies safety issues, as occurred recently with respect to the spread of antibiotic resistant bacteria in riboflavin supplemented feed (Rychen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Riboflavin exists in various organs of the human body, promoting metabolism and normal vision [ 18 ]. Thus, riboflavin plays an important role in cell proliferation and growth [ 19 ]. Riboflavin is an isopropylamine derivative with a side chain of ribitol, mainly formed from the direct precursors GTP and ribulose 5-phosphate through a series of reactions catalyzed by riboflavin synthase [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid a lack of vitamin E in organic herds during winter feeding [98], such differentiated recommendations, which consider not only the animals' needs but also the varying provision by different feeds, urgently need to be developed. Riboflavin (vitamin B2) deficiency occurs for instance in livestock birds, especially in growing chicks and broilers, and symptoms are severe and relevant to health and welfare [39]. Therefore, non-supply is no option.…”
Section: Current Use Of Vitamins and Its Alternatives In Organic Live...mentioning
confidence: 99%
“…Another problem associated with B vitamins is that these are nowadays mostly produced by microorganisms that have been genetically modified [37] which is categorically forbidden in organic production. The lack of GM-free vitamin B manufacturing in Europe reinforces the vulnerability of the vitamin feed supply of organic farming [38,39].…”
Section: Introductionmentioning
confidence: 99%